Biomechanical model of the basic snatch techniques - Formicola, D. (EWF Scientific Magazine, 2015)
The upward trajectory that the barbell completes during the execution of the Snatch generates great interest from the scientific literature that deals with sports biomechanics, as it is a demonstration of how it is possible to develop specific motor strategies that can lift a load, which, in the specific case of this movement, can reach almost two and a half times the body weight (Liu Xiaojun, 2013 world record holder, who lifted 176 kg in the Snatch, about 2.3 times his body weight of 76.4 kg). The trend of the barbell trajectory is represented by a characteristic "S" shape and is delineated by the mechanical contribution of the joint levers that, in altering their spatial disposition during the entire evolution of the movement, mainly generate three propulsive periods: 1) the pull, characterised by the action of the lower limbs and the rearward displacement of the barbell; 2) the thrust, which involves raising the pelvis and a forward displacement of the barbell; 3) the push, when the shoulders are fully raised with the simultaneous extension of the lower limbs to allow the barbell to reach maximum height. In the modern evolution of the technique, aimed at improving the mechanical efficiency of lifting increasingly heavier loads producing increasingly faster actions, the trajectory of the barbell tends to assume a less curved trends. Two examples of technical variations of this type are (1) the changes that are occurring in the "double knee bend" phase (plyometric action leg) that, to reduce the horizontal displacement in the first pull, loses the countermovement, becoming therefore, a "single knee bend", and (2) the exasperation of the explosive component of the thrust through the accentuation of the jump action at the end of the triple joint extension of the lower limbs, in order to limit the rotation of the arms at the maximum height of the barbell in the push. However, in the Snatch, the barbell goes beyond the athlete's centre of gravity with a change in the vertical direction of the extension of the upper limbs and a relative variation of the dynamic vertical thrust: when the arms are stretched downwards, the legs develop a vertical acceleration of the barbell through a linear inertial force that exploits the reaction force generated by the support surface; whereas, when the arms rotate upwards, the upward force of the barbell is ensured by the moment of inertia produced by the interaction between the athlete's centre of gravity and that of the barbell. Based on the morphological and athletic characteristics, some lifters prefer to coordinate the rotation of their weight mass as opposed to that of the barbell, while others fail to control the rotations of the barbell while maintaining constant the positions of the inertial mass of their body. The elevation of the upper limbs during the third push therefore requires the management of a roto-translation strategy of the centres of gravity of the athlete mass-barbell mass couple, whose effect inevitably has an impact on the curve of the barbell trajectory. Much research is underway in the field of sports biomechanics regarding the weight contribution of the athlete and the barbell, in order to define a standardised efficient execution of the modern technique of the Snatch and to minimize the dispersion of muscle forces engaged in the development of the performance of Olympic Weightlifting.